VIRUSES AND THEIR EFFECTS ON LIVING ORGANISMS - Nugmanova Komila Isroiljon qizi (Web of Journals Publishing, 2023)
This article explores the diverse effects of viruses on living organisms, shedding light on their impact at the molecular, cellular, and organismal levels. Through a comprehensive literature analysis, this study delves into the mechanisms by which viruses interact with host organisms, the methods employed in virus research, and the resultant implications for health and ecosystems. The results provide a nuanced understanding of the complex relationships between viruses and living organisms, offering insights into potential avenues for future research and the development of preventive measures.
Keywords: Viruses, host-pathogen interactions, molecular mechanisms, cellular impact, organismal response, virus research methods, health implications, ecosystems, preventive measures.